The future of the university: four models of development (Journal of Educational Sciences, 2023)
The development of a market economy, the COVID-19 pandemic, globalization, digitalization, the development of the online sphere, the crisis of values and many other factors contribute to changing the role of universities in the modern world. While a number of researchers believe that after a protracted pandemic, the axis of world higher education will return to its former traditional course, others are confident that universities will soon disappear altogether, being thrown overboard by massive online courses. The main purpose of this study is to analyze and present the main scenarios for the development of universities in the future, based on the research of leading philosophers, as well as to highlight the general prospects for the development of higher education. The main methods of this foresight research are content analysis of research literature, descriptive method of future scenarios, as well as their historical and philosophical analysis. The study is of a review and theoretical nature. The results and discussions present four main "ideas" of the university, the goals and social legitimacy of which are now accepted in society as true and indisputable. This study will complement the ideas about the future of higher education, the transformation of universities under the influence of globalization, market capitalism and other factors. Its results will be useful to teachers of higher educational institutions, philosophers of education and anyone interested in the problems of higher education.Key words: philosophy of education, neoliberalism, classical university, MOOC courses, online courses, transformation of education, crisis of values.